A comparative study on speaking skill among female linguistic preparation students at Sunnah Islamic University (A study among female graduates from Salafi institutes and modern institutes) - Muhammad Sapii Harahap; Annisa Salsabilla Albarad; Tiy Kusmarabbi Karo; Ahmad Afandi; Isnawati Isnawati; Fatkhur Rohman (Universitas Muhammadiyah Enrekang, 2022)
The research questions are (1) How is the speaking skill ability of linguistic preparation students graduating from Salafi institutes?, (2) How is the speaking skill ability of linguistic preparation students graduating from modern institutes?, (3) What is the result of the comparison between the two in speaking skill ability? The research methodology used in this research is qualitative field research. Then collect data through observation, interview, and documentation. The research results obtained from the analysis, including (1) female language preparation students who graduated from Salafi schools are: (a) female language preparation students “A” are many female students who are skilled in the Arabic language, and use the rules of grammar and morphology correctly. (B) Linguistic Preparation Students “B” I understand how to structure a sentence and use the rules of grammar and morphology well, but little of them apply it. (2) Female students graduating from modern institutes are: (a) Female students of linguistic preparation “A” who lack in sentence structure and the use of grammar and morphology rules. (b) Language Preparation B students are the most skilled and active in Arabic, but there are also some of them who are less able to speak Arabic. (3) A comparison between the two groups, that is, female students graduating from Salafi institutes excelled in speaking the Arabic language. As a result of the students’ speaking skill, linguistic preparation, from a close perspective, which is the result of the placement test, it shows that the students obtained an average grade with a grade of very good